Untargeted metabolomic profiling on the effect of ginger on rat hepatic changes during ageing - Sophia Ogechi Ekeuku; Ahmad Baihaqi Ahmad Shahzalli; Jen Kit Tan; Suzana Makpol (Journal of Functional Foods, 2024)
Studies have shown various beneficial properties of ginger to improve human health. This study aimed to elucidate the effects of ginger on liver metabolomes and metabolic pathways in rats. Three-month-, 9-month-, and 21-month-old male Sprague Dawley (SD) rats were divided into control and treated groups. Rats in the control and treated groups were given 1 mL of distilled water and 200 mg/kg body weight/day of ginger, respectively, via oral gavage for 3 months. Liver tissue was harvested at the end of the study for metabolomic analysis. Our results showed that metabolites involved in pyrimidine and purine metabolism, nicotinate and nicotinamide metabolism, pantothenate and CoA biosynthesis, glutathione metabolism, arginine and proline metabolism, alanine, aspartate and glutamate metabolism, D-glutamine and D-glutamate metabolism and arginine biosynthesis were altered by ageing. Ginger supplementation reversed alterations caused by age in pyrimidine and glutathione metabolism in young rats and nicotinamide and nicotinate metabolism in adult rats. Of great interest was the upregulation of glutamate, a metabolite intermediate involved in amino acid metabolism. Our findings suggest that supplementation with ginger modulates the changes in metabolic pathways in the liver from a young age and may be beneficial in providing therapeutic options for slowing or even reversing the effects of ageing and delaying the progression of age-related diseases.